Rodent management issues in a Solomon Islands healthcare setting: an infection prevention and control response and preliminary findings - Croom, Katie; Kwaina, Majory; Mason, Matt (International Journal of Infection Control, 2025)
Background: The National Referral Hospital (NRH) in Honiara, Solomon Islands has faced a large-scale rodent infestation for decades posing significant risks to patient safety, infrastructure, and healthcare delivery through issues such as patients receiving bites and medical stores being contaminated. Aim: This study aimed to implement and evaluate a comprehensive rodent management programme to reduce rodent populations and associated infection risks at the NRH. Methods: A two-phase approach was adopted: Meeting pre-conditions identified through consultation with hospital staff and an external pest control company. Implementation of rodent extermination using brodifacoum bait stations throughout the NRH. The programme’s effectiveness was assessed through monitoring bait consumption rates and counting collected deceased rodents. Findings: Following implementation, a significant decrease in rodent populations was observed: A total of 110 deceased rodents were recorded in the initial 1-month period. Bait consumption decreased from an average of 29 blocks per day 3 weeks post-implementation to 3.57 blocks per day after 6 months. No further rodent bites to patients or damage to medical equipment were reported after March 2024. Conclusion: The rodent management programme demonstrated substantial success in reducing rodent populations at the NRH, improving patient safety and healthcare delivery. However, long-term commitment and resource allocation are necessary to maintain these improvements.